Engine Testing of Gasoline and E5, E10, E15 and E20 Ethanol Blends - Mohammad Asyraf bin Mohammad Hatta, Mohammad Asyraf (2008)
The project is about comparing the ethanol blends with neat gasoline. The purpose of the study is to compare the performance of the engine prior to the usage of neat gasoline and ethanol blends. A study of Alvydas Pikunas et. al. however shown that there is possibility of engine performance increment due to the properties of the ethanol in the blends.